Effects of cognitive behavior therapy-based psychoeducation program on mental health among LGBTQ+ high school students - Manee, Thanawat Suwan; Supreeyaporn, Nanthaka (Kasetsart Journal of Social Sciences, 2026)
Despite the increasing prevalence of mental health issues among LGBTQ+ high school students, research on prevention interventions has remained limited. This quasi-experimental study aimed to develop and evaluate the effectiveness of Rainbow Psycho-care, a CBT-based psychoeducational group program to promote mental health in LGBTQ+ high school students. Thirty participants aged between 15 and 17 years were recruited and assigned to the experimental group (n = 15) and the control group (n = 15). Participants in the experimental group received a 12-session intervention, while those in the control group received no intervention. The Depression Anxiety Stress Scale (DASS-21) and protective factors on mental health problems for LGBTQ+ high school student questionnaire were administered at pre-intervention, post-intervention, and 1-month and 3-month follow-ups. The results indicated significant differences between the groups in stress, anxiety, and depression levels at the post experiment, as well as at 1-month and 3-month follow-up periods (p < .05), with a large effect size (η2 p > 0.14). Additionally, resilience and self-esteem differed significantly between groups across the assessment points (p < .05), with a large effect size (η2 p > 0.14). However, positive psychology levels did not differ significantly (p > .05). These findings suggested that Rainbow Psycho care effectively reduces stress, anxiety, and depression levels among LGBTQ+ high school students. Moreover, Rainbow Psycho-care demonstrated potential benefits in enhancing protective factors such as resilience, self-esteem, and positive psychology for LGBTQ+ high school students.